Phase and Defect Engineering of MoS2 Stabilized in Periodic TiO2 Nanoporous Film for Enhanced Solar Water Splitting. Issue 5 (12th December 2018) - Guo, Limin; Zhong, Caifu; Shi, Li; Ju, Licheng; Wang, Xiaohui; Yang, Daquan; Bi, Ke; Hao, Yanan; Yang, Yang
Abstract: Phase and defect engineering of the heterostructured MoS2 @TiO2 nanoporous film is investigated to achieve a broad solar spectrum light absorption and high solar water splitting efficiency. The phase transition from the semiconducting 2H‐MoS2 to the metallic 1T‐MoS2 is achieved by a hydrothermal exfoliation treatment. Experimental studies elucidate that the solar water splitting activity is greatly improved by forming 1T‐MoS2 along with increasing S‐vacancies because of the significantly enhanced surface plasmon resonance. The mixed‐phase MoS2 @TiO2 film shows a high H2 yield rate of 308 µmol h −1 cm −2 and long‐term durability for 30 h, which is superior to the state‐of‐the‐art catalysts for solar water splitting. This study offers a universal and efficient avenue to rationalize the plasmonic catalysts for solar water splitting and other energy and environmental applications. Abstract : Phase‐/defect‐engineered MoS2 @TiO2 catalysts are rationally designed to enhance the plasmonic effect for solar H2 evolution. The phase transition from 2H‐ to 1T‐MoS2 and S‐vacancies are responsible for the enhanced localized surface plasmon resonance, leading to a superior H2 yield rate. This work offers an innovative strategy to explore plasmonic catalysts with low cost and long‐term durability.